Misleading nomenclature in the IARC Monographs Programme: a straightforward solution to improve accuracy and clarity - Miguel López-Lázaro (Exploration of Medicine)
The International Agency for Research on Cancer (IARC) Monographs Programme plays an important role in cancer prevention by identifying potential carcinogenic hazards. However, the terminology used in IARC’s classifications and Monographs can confuse the public, health professionals, and policymakers. Terms like “carcinogenic to humans” imply causation, although classifications only indicate increased risk under certain conditions. For example, the lifetime incidence of mesothelioma among firefighters is approximately 14 in 10,000, compared to 7 in 10,000 in the general population. Despite doubling the risk, occupational exposure as a firefighter does not cause this type of cancer in 9,986 out of 10,000 firefighters. However, the IARC concludes that “occupational exposure as a firefighter causes mesothelioma” (IARC Working Group on the Identification of Carcinogenic Hazards to Humans. Occupational Exposure as a Firefighter. Lyon: IARC; 2023. pp. 1–730. PMID: 37963216). In addition, the lack of essential information about dosage and context in the IARC carcinogen lists can lead to agents with health benefits under certain conditions (e.g., solar radiation, red meat consumption, approved drugs) being perceived as universally harmful, discouraging beneficial exposures, behaviors, or treatments. Here, I propose renaming the groups of agents classified by the IARC and adding basic labels to specific agents to improve the accuracy and interpretability of the IARC classification lists. These adjustments do not interfere with the IARC’s objective of identifying potential hazards, are easy to implement, and enhance accuracy and clarity, providing stronger support to guide cancer prevention strategies.